Functional, Phytochemical and Processing Properties of Proso Millet (Panicum milaceum. L)- A Potential Nutri Millet - S. K. Mathanghi; V. Perasiriyn; A. Karthiayani (Recent Progress in Plant and Soil Research Vol. 3, 2021)
Proso millets are eco-friendly smart grains rich in minerals and phytochemical compounds that preserve the health of the individuals. The bioactives present in proso millet gives protection against metabolic syndromes and lifestyle diseases. Hypoglycemic effects of millets, in general are much appreciated and currently millets are used in valorizing the food products due to its functional key elements. In spite of its health benefits and agronomical and economical prospective, millets lost its fame especially in developing countries and it has not reached the massive population may be due to processing difficulty and reduction in production area. This article presents reviews and research investigations about agronomical advantages, post harvest handling protocols, nutraceutical and functional properties and methods of valorizing the proso millet.